2017
DOI: 10.1002/pc.24362
|View full text |Cite
|
Sign up to set email alerts
|

Compressive capacitance relaxation of carbon black filled silicone rubber composite

Abstract: The changes in the capacitance of carbon black filled silicone rubber composite during the compressive stress relaxation, which is defined as the “compressive capacitance relaxation,” is researched. During the compressive stress relaxation, the capacitance of the composite increases gradually and tends to be stable over time. Based on the viscoelastic theory, the mathematical model for the compressive capacitance relaxation is established. The capacitance relaxation times and the stable normalized capacitance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…When it was combined with fluorine resin to form coatings, due to the influence of surface shape, particle size, surface wetting agent, and solvent in the coating system, there were many pores between resin and carbon black, which affected the compactness of the whole coating. The more carbon black that was added, the more serious the defect between the resin and carbon black was, which affected the resistance of the coating to moisture and oxygen permeation [24]. The mechanical properties, optical properties, and infrared spectroscopy tests showed that the black paste yielded better properties when its content was 0%-3.0%.…”
Section: Resultsmentioning
confidence: 99%
“…When it was combined with fluorine resin to form coatings, due to the influence of surface shape, particle size, surface wetting agent, and solvent in the coating system, there were many pores between resin and carbon black, which affected the compactness of the whole coating. The more carbon black that was added, the more serious the defect between the resin and carbon black was, which affected the resistance of the coating to moisture and oxygen permeation [24]. The mechanical properties, optical properties, and infrared spectroscopy tests showed that the black paste yielded better properties when its content was 0%-3.0%.…”
Section: Resultsmentioning
confidence: 99%
“…are common matrices for stretchable electronics. [23][24][25] There is currently a great deal of research interest in the optimization of three-dimensional (3D) interconnected heat dissipation pathways in matrix. 26 Especially, designing a unique stretchable structure such as bulking and wavylike structure, enabling them to absorb large scales of strain without serious deformation, which has displayed great potential for various advanced electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone rubber possesses the environment friendly, excellent fatigue resistance, excellent aging-resistance, and wide working temperature range, which has been extensively applied to manufacture flexible sensor products. [23][24][25][26][27][28] But most studies deals with wet-processing of CNTs in silicone rubber involving organic liquids to avoid their damage, making them difficult and cumbersome for industrial production. [29] So the technology challenges always maintain for improved dispersion and less damage of SWCNTs through dry processes.…”
Section: Introductionmentioning
confidence: 99%